PELATIHAN LEADERSHIP LIFE SKILL DALAM MEMPERSIAPKAN WIRAUSAHA BAGI SANTRI PESANTREN - Ahmad Ahmad; Lamto Widodo; Dewi Yuliana; Rio Alfandy (PROSIDING SERINA, 2021)
Entrepreneurs who quickly understand consumer desires, then manifest in the form of products that suit their needs, then the entrepreneur has actually made the right decision and has gone through stages as a creative person and has good leadership knowledge. A person can be said to have good leadership skills if he has some special abilities in attitude. Attitudes needed for leadership skills include social skills, wisdom, courage, and being able to make decisions about the problems at hand. Leadership is important because leadership is the key to the success of efforts to achieve goals. With good leadership strength, obstacles and obstacles can be faced. The most important purpose of this entrepreneurship training is to help the students to be able to see business opportunities to be developed and to introduce the obstacles that usually occur when having a business. In various obstacles, it is hoped that the students have strong leadership foundations so that they have the courage to make decisions. The method used in this training uses lectures with examples and pictures so that students can easily understand the process of starting a business, capturing opportunities from consumers, and understanding leadership attitudes. The results of the evaluation of this training, that the benefits of the training were considered very good, namely about 86% of the participants felt the benefits of this training.